AIAA SPACE 2009 Conference &Amp; Exposition 2009
DOI: 10.2514/6.2009-6584
|View full text |Cite
|
Sign up to set email alerts
|

Subcooling Cryogenic Propellants for Long Duration Space Exploration

Abstract: The use of cryogenic propellants such as hydrogen and oxygen is crucial for exploration of the solar system because of their superior specific impulse capability. Future missions may require vehicles with the flexibility to remain in orbit or travel in space for months, necessitating long-term storage of these cryogens. One powerful technique for easing the challenge of cryogenic fluid storage is to remove energy from tlie cryogenic propellant by isobaricly subcooling them below their normal boiling point prio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…However, when the maximum pressure increases, the tank becomes heavier, leading to aircraft performance losses. [131]; simplified process for maintaining the subcooling level through isothermal pressurization and isobaric heating for low-pressure pump inlet requirements.…”
Section: Realistic Tank Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when the maximum pressure increases, the tank becomes heavier, leading to aircraft performance losses. [131]; simplified process for maintaining the subcooling level through isothermal pressurization and isobaric heating for low-pressure pump inlet requirements.…”
Section: Realistic Tank Conditionsmentioning
confidence: 99%
“…Figure 8. Realistic thermodynamic tank conditions adapted from Mustafi et al[131]; simplified process for maintaining the subcooling level through isothermal pressurization and isobaric heating for low-pressure pump inlet requirements.…”
mentioning
confidence: 99%
“…Its characteristics are that liquid hydrogen/liquid oxygen were subcooled to 15 and 66.67 K, respectively, in 2 h. The devices obtaining subcooling degree consisted of heat exchangers, compressors, pumps, a skid-mounted rack truck and so on. Through many studies, [4][5][6][7][8][9][10][11][24][25][26][27][28][29][30][31][32] it can be found that many verifications of subcooled propellants, including large-scale production, storage, transportation, filling and igniting experiments of engine, were conducted by NASA.…”
Section: Analysis Of Application Cases For Many Countriesmentioning
confidence: 99%
“…Three key aspects of this technology were demonstrated as follows: the feasibility of producing high-volume LO 2 densification, achievement of top-to-bottom recirculation of LO 2 and obtainment of thermal stratification conditions in a flight-weight LO 2 tank using unique processing method. Mustafi et al [7,8] proposed a thermodynamic cryogen subcooler, which provided an effective method for isobaric subcooling of cryogenic propellants on the launch pad with a relative small system. For Ares V launch pad, Johnson et al [9] determined that liquid methane could be densified by subcooling it to 93 K, so as to prevent over-pressurization of the propellant tanks on the lunar surface during 210 days.…”
Section: Introductionmentioning
confidence: 99%
“…Johnson [5] determined that the LCH4 should be cooled to 93 K from 111 K to extend in-orbit time on the lunar surface. Mustafi [6] explored the beneficial effect of subcooled cryogenic propellants on the launch pad for long-term storage of cryogenic propellants in space. Baik [7] reported that when the liquid hydrogen density increased to 8% and the liquid oxygen density increased to 10%, the gross lift-off weight of a cryogenic rocket could reduce by up to 20%.…”
Section: Introductionmentioning
confidence: 99%